2012
DOI: 10.7314/apjcp.2012.13.11.5753
|View full text |Cite
|
Sign up to set email alerts
|

Modulating Effect of Lupeol on the Expression Pattern of Apoptotic Markers in 7, 12-Dimethylbenz(a)anthracene Induced Oral Carcinogenesis

Abstract: Apoptosis, also known as cell suicide or programmed cell death, removes unwanted and genetically damaged cells from the body. Evasion of apoptosis is one of the major characteristic features of rapidly proliferating tumor cells. Chemopreventive agents inhibit or suppress tumor formation through apoptotic induction in target tissues. The aim of the present study was to investigate the pro-apoptotic potential of lupeol during 7,12-dimethylbenz(a) anthracene (DMBA) induced hamster buccal pouch carcinogenesis. Top… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 27 publications
2
10
0
Order By: Relevance
“…Previous studies from our laboratory reported the chemopreventive potential as well as proapoptotic, anti-inflammatory and anti-angiogenic potential of lupeol in DMBA induced hamster buccal pouch carcinogenesis. [ 69 70 ] Manimaran et al .,[ 71 ] reported that lupeol showed potent anti-cellproliferative, anti-inflammatory and anti-angiogenic potential during DMBA induced hamster buccal pouch carcinogenesis. Rao et al .,[ 72 ] demonstrated the anticancer efficacy of squalene in azoxy methane induced rat colon carcinogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies from our laboratory reported the chemopreventive potential as well as proapoptotic, anti-inflammatory and anti-angiogenic potential of lupeol in DMBA induced hamster buccal pouch carcinogenesis. [ 69 70 ] Manimaran et al .,[ 71 ] reported that lupeol showed potent anti-cellproliferative, anti-inflammatory and anti-angiogenic potential during DMBA induced hamster buccal pouch carcinogenesis. Rao et al .,[ 72 ] demonstrated the anticancer efficacy of squalene in azoxy methane induced rat colon carcinogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…In the seeds, the terpenoids detected using gas chromatography were β -sitosterol, stigmasterol, lupeol, campesterol, and squalene [14, 15]. Interestingly, lupeol was found to possess anticarcinogenic [16], antinociceptive, and anti-inflammatory properties [17]. No flavonoid like quercetin, myricetin, luteolin, kaempferol, or apigenin was detected in the methanolic extract of P. speciosa seeds using a reversed-phase high performance liquid chromatography [18], but it was noted to be present in the ethanolic extract when screened using a colorimetric assay [10].…”
Section: Chemical Compoundsmentioning
confidence: 99%
“…A large number of oral cancer chemopreventive agents were reported against 7,12-dimethylbenz(a)anthracene (DMBA)-induced oral carcinogenesis (Baskaran et al, 2012;Manoharan et al, 2012a;2012b;Prabhakar et al, 2012).…”
Section: Research Articlementioning
confidence: 99%